STP Marketing Strategy Model for Salted Egg MSMEs: Product Differentiation Analysis Based on Production Technology: Bahasa Inggris - Intan Puspitasari; May Shinta Retnowati; Rif'atu Salimah (Al-Muamalat: Journal of Islamic Economics Law, 2026)
ENGLISH (Main Problem of Research) This study highlights the weak competitiveness of small and medium enterprises (SMEs) in salted eggs due to low innovation in production processes and marketing strategies. A lack of attention to cleanliness, unclear market segmentation, and manual marketing become obstacles in reaching modern consumers. (Research Objectives) The purpose of this study is to review how consumers make decisions in consuming Tegal salted eggs produced by the UMKM Tegal salted eggs and to evaluate the effectiveness of manual and digital processes in terms of quality and market reach (Methodology) The approach used combines STP theory (Segmentation, Targeting, Positioning), Marketing Mix (7P), as well as a qualitative analysis approach. (Results) The results show that digitalization in production and promotion processes is more effective in building positive consumer perceptions, expanding the market, and increasing repeat orders. INDONESIA (Masalah utama dari penelitian) Penelitian ini menyoroti lemahnya daya saing UKM telur asin akibat rendahnya inovasi dalam proses produksi dan strategi pemasaran. Kurangnya perhatian terhadap kebersihan, segmentasi pasar yang tidak jelas, dan pemasaran manual menjadi hambatan dalam menjangkau konsumen modern. (Tujuan penelitian) Tujuan penelitian ini adalah untuk meninjau bagaimana konsumen membuat keputusan dalam mengonsumsi telur asin tegal produksi